Tort liability of the state - Korpič - Horvat, Etelka (Anali PAZU HD, 2022)
In the articlethe author discusses questions that refer to the tort liability of the state. It is the aggrieved person’s right to compensation for damage caused through unlawful actions in connection with the performance of any function or other activity by a person or authority performing such function or activity within a state or local community authority or as a bearer of public authority (Article 26 of the Constitution). The author presents the tort liability of the state in connection with the right to life, as one of the paramount values of democratic societies.Through case No. Up-679/12, dated 16 October 2014, decided by the Constitutional Court of the Republic of Slovenia, the author underlines that the state is not liable for damages only if it proves that it did everything in its power to eliminate the risk for the life and health of the individuals in the case of a damaging incident.The protection of human life and healthrequires that very strict criteria be employed in the assessment as to whether to exclude the liability of the state.